2007
DOI: 10.1161/01.hyp.0000252409.36927.05
|View full text |Cite
|
Sign up to set email alerts
|

Marinobufagenin Stimulates Fibroblast Collagen Production and Causes Fibrosis in Experimental Uremic Cardiomyopathy

Abstract: Abstract-We have observed recently that experimental renal failure in the rat is accompanied by increases in circulating concentrations of the cardiotonic steroid, marinobufagenin (MBG), and substantial cardiac fibrosis. We performed the following studies to examine whether MBG might directly stimulate cardiac fibroblast collagen production. In vivo studies were performed using the 5/6th nephrectomy model of experimental renal failure (PNx), MBG infusion (MBG), PNx after immunization against MBG, and concomita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
235
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(255 citation statements)
references
References 30 publications
19
235
1
Order By: Relevance
“…[32][33][34] EDLF increases the calcium influx in vascular smooth muscle cells by blocking Na þ /K þ -ATPase and longterm ouabain administration and MBG stimulates fibroblast, which in turn leads to collagen accumulation in the wall of artery and in rats it causes stiffness of artery. 14,35 We found an inverse relationship between plasma EO and the augmentation index of carotid artery as well as positive correlations between levels of urinary EO and b-stiffness index and pulse wave velocity of carotid artery (Figure 1), which suggests that EO have a role in development of artery stiffness. Some studies have shown that the arterial stiffness relates with age, body mass index, systolic blood pressure, diabetes and hypertension and independently associates decreased glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…[32][33][34] EDLF increases the calcium influx in vascular smooth muscle cells by blocking Na þ /K þ -ATPase and longterm ouabain administration and MBG stimulates fibroblast, which in turn leads to collagen accumulation in the wall of artery and in rats it causes stiffness of artery. 14,35 We found an inverse relationship between plasma EO and the augmentation index of carotid artery as well as positive correlations between levels of urinary EO and b-stiffness index and pulse wave velocity of carotid artery (Figure 1), which suggests that EO have a role in development of artery stiffness. Some studies have shown that the arterial stiffness relates with age, body mass index, systolic blood pressure, diabetes and hypertension and independently associates decreased glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 71%
“…EO take part in the development of hypertension through increased sympathetic tone, and in direct prohypertrophic effects on myocytes of heart and arteries, as well as causing collagen overproduction and cardiomyopathy in uraemic rat heart. 13,14 These processes can lead to cardiac hypertrophy in vivo. 17 In our study, we have found association between left ventricular diastolic dysfunction (E/A) and level of plasma EO in HT þ DM þ CKD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active immunization against marinobufagenin attenuates most of the biochemical, physiological and morphological features of uremic cardiomyopathy in animals subjected to partial nephrectomy. 135,136 Exposure to very small amounts of marinobufagenin (and of other cardiotonic steroids) virtually identical to the circulating plasma concentrations seen in experimental and clinical renal failure directly stimulated the production of collagen in primary cultures of cardiac fibroblasts. 134,135 Again, this effect required signaling through the Na + /K + -ATPase-Src-EGFR cascade.…”
Section: Role Of Cardiotonic Steroids In Renal Failurementioning
confidence: 99%
“…Ultimately, this chain of signaling events would alter cellular functions and cell growth in a cell-specific manner (5, 9 -12). For instance, we and others have demonstrated that ouabain-induced activation of ERK and PI3K/Akt/mTOR pathways are responsible for cell growth stimulation in transformed cell lines, in primary cultures, as well as in vivo (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%